Short Communication: The species and body size composition of pelagic fishes that caught by troll line in the fish landing of Sendang Biru, East Java, Indonesia - DEWI HIDAYATI; BUGGIE OCLANDHI; NOVA MAULIDINIA; NOOR NAILIS SA’ADAH; AWIK PUJI DYAH NURHAYATI (Society for Indonesian Biodiversity, 2019)
Abstract. Hidayati D, Oclandhi B, Maulidinia N, Sa’adah NN, Nurhayati APD. 2019. Short Communication: The species and body size composition of pelagic fishes that caught by troll line in the fish landing of Sendang Biru, East Java, Indonesia. Biodiversitas 20: 1764-1769. Troll line is the most used pelagic fishing gear for fishermen in Sendang Biru, the part of Indian ocean at East Java, which have an impact on the catch composition. The study was aimed to obtain data on species composition and size of pelagic fish caught in troll line in Sendang Biru, East Java, Indonesia. Fish samples were collected from nine different vessels landed in Sendang Biru for three days in April 2018. The composition of fish species was measured based on relative abundance. The fish size composition was obtained by measuring fork length which is also used to determine the stage of development of juvenile (Jv) or adult (Ad) fish. The results of the research showed there were four pelagic fish species which dominated by Katsuwonus pelamis or skipjack tuna (50.05%) and Thunnus albacares or yellowfin tuna (47.95%) and a small amount of Coryphaena hippurus and Makaira mazara. According to the body size, the fish caught by troll line in Sendang Biru is dominated by adult skipjack tuna (41-60 cm) and juvenile yellowfin tuna (21-78 cm).